2007
DOI: 10.1007/s11882-007-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Are there reasons why adult asthma is more common in females?

Abstract: Many epidemiological studies suggest that women are at increased risk of developing adult-onset asthma and also suffer from more severe disease than men. These gender differences appear to be the product of biological sex differences as well as sociocultural and environmental differences. The biological sex differences include genetic, pulmonary, and immunological factors. There is compelling evidence that sex hormones are major determinants of at least these biological sex differences. This paper explores the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
120
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 70 publications
10
120
2
6
Order By: Relevance
“…Although many reasons have been hypothesized, it is believed that reproductive hormones may partly explain these sex differences (30). Our study shows that ever having smoked is a risk factor for adult-onset asthma, but only for women.…”
Section: Original Researchmentioning
confidence: 51%
“…Although many reasons have been hypothesized, it is believed that reproductive hormones may partly explain these sex differences (30). Our study shows that ever having smoked is a risk factor for adult-onset asthma, but only for women.…”
Section: Original Researchmentioning
confidence: 51%
“…5 Among adults, epidemiological studies have demonstrated that the prevalence of asthma is higher among females than among males. [6][7][8] The relationship between sex hormones and asthma has been evaluated in several studies. 9,10 Sex-related differences in the risk, incidence and pathogenesis of a variety of lung diseases exist in humans.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to tobacco consumption, it has been suggested that women may be at greater risk than men of developing respiratory health problems and susceptibility to lung cancer later in life, as a result of the fact that smoking affects airway development during childhood [3][4][5][6]. In addition, studies have found that sex-specific factors may be important etiologic factors in the development of asthma [7,8], pulmonary diseases [9] and lung cancer [10].…”
Section: Introductionmentioning
confidence: 99%